Education 3410. Comparative Educational Administration. Program 23 - Parsons, Llewellyn, 1930- (Teacher) (MUN Extension Service, 1979)
Based on a series of studies of grade eleven studies conducted during the 1970's, Dr. Parsons examines the factors influencing the vocational and career choices made by students in Newfoundland and Labrador. These factors include the occupation and educational level of parents; family size; financial situation; and the content of the educational program experienced.